Strategies Against Examination Malpractice in Tertiary Institutions in Nigeria: The Position of The Library in Service Delivery - Ahmed, Hasanah Kudirat (POMLIF Journal of Library and Information Science, 2021)
In recent years examination malpractice has become one of the most pernicious maladies afflicting our educational system from the primary school level to the tertiary level of education. Therefore, this paper takes a critical look into the meaning of examination malpractice, causes of examination malpractice, why students fail examinations and also x-rayed the library strategies against examination malpractices. More importantly, recommendations were proffered on how the library could be a remedy to this social malaise.